2021
DOI: 10.3390/metabo11090634
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decrease in Hepatic Geranylgeranoic Acid Content in C3H/HeN Mice and Its Oral Supplementation Prevents Spontaneous Hepatoma

Abstract: Geranylgeranoic acid (GGA) has been developed as a preventive agent against second primary hepatoma. Recently, GGA was reported to induce cell death in human hepatoma cells via TLR4-mediated pyroptosis. We have reported that GGA is enzymatically biosynthesized from mevalonic acid in human hepatoma-derived cells and that endogenous GGA is found in most organs of rats. In addition, we found that upregulation of endogenous GGA levels by zaragozic acid A (ZAA) induced cell death in human hepatoma-derived cells. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 28 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…HT is one of the main phenols present in VOO with interesting health benefits [11][12][13][14]. On the other hand, SQ, another important compound present in VOOs and olives, also has antitumor properties against several types of cancer, such as skin, breast and colon cancer [18][19][20][21][22][23][24]. Interestingly, both isolated compounds did not promote the inhibition of highly invasive breast cells in previous published works [17,26], but together at certain concentrations, appeared to promote the inhibition of breast cancer cells' growth and apoptosis, as well as increasing DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HT is one of the main phenols present in VOO with interesting health benefits [11][12][13][14]. On the other hand, SQ, another important compound present in VOOs and olives, also has antitumor properties against several types of cancer, such as skin, breast and colon cancer [18][19][20][21][22][23][24]. Interestingly, both isolated compounds did not promote the inhibition of highly invasive breast cells in previous published works [17,26], but together at certain concentrations, appeared to promote the inhibition of breast cancer cells' growth and apoptosis, as well as increasing DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when squalene is ingested by diet, squalene-derived sterols accumulate in the cells and β-hydroxy-βmethylglutaryl-CoA reductase (HMG-CoA reductase) is inhibited [21]. Furthermore, recent evidence has shown that squalene excess leads to an accumulation of farnesyl pyrophosphate (FFP), which could be related to the suppression of carcinogenesis [22,23]. In fact, dietary ingestion of SQ can inhibit colon cancer development in vivo [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we would like to discuss the relationship between CYP3A4 enzyme and hepatoma from the viewpoint of inhibiting hepatocarcinogenesis, which is one of the biological activities of GGA. The liver normally expresses high levels of MAOB and biosynthesizes carcinogenic inhibitory GGA [7,12,31]. However, the enzymatic activity of MAOB is decreased at the site of hepatoma, and a classical paper described that the higher the grade of hepatoma, the lower the activity of MAOB [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium, which is present in cigarettes, has been strongly associated with HCC [ 129 ]. Lastly, it has been shown that hepatic monoamine oxidase B (MAOB) is involved in the biosynthesis of geranylgeranoic acid (GGA) (found in animal models and hepatoma cell lines) which is believed to prevent hepatocarcinogenesis [ 130 , 131 ]. Nevertheless, smoking tobacco inhibits MABOB, which can lead to suppressing GGA and its preventive effect of hepatocarcinogenesis [ 132 ].…”
Section: Role Of Smoking In Hccmentioning
confidence: 99%